PENINGKATAN LITERASI TEKNOLOGI CVT KENDARAAN RODA DUA PADA SEKEHA TERUNA TERUNI HITA SHANTI DI LINGKUNGAN GRIYA PAGUTAN INDAH MATARAM - Mara, I Made; Allo Padang, Yesung; Wirawan, Made; Nuarsa, I Made; sinarep, Sinarep (Jurnal Bakti Nusa, 2025)
Continuously variable transmission (CVT) technology is currently something that is very commonly used in motorcycles for various reasons of practicality in use. This encourages the importance of CVT technology literacy in motorcycles to emerge in this context, because the CVT system has characteristics that inherently support fuel efficiency. CVT allows riders to enjoy smooth transmission ratio changes without the need for manual gear shifting. This is an advantage especially in urban traffic situations that often involve stop-and-go patterns, where the CVT system can keep the engine operating at an efficient speed. However, in order for the benefits of CVT to be felt to the maximum, riders need to understand how this technology works. CVT technology literacy includes knowledge of how to use the CVT system optimally, avoiding riding styles that can put excessive stress on the transmission, and understanding the maintenance needed to maintain CVT performance. Riders who are educated in CVT technology will apply fuel-efficient riding techniques, such as avoiding sudden acceleration or unnecessary braking, which will not only increase fuel efficiency but also extend the life of the CVT. In addition, regular maintenance, such as checking and replacing the CVT belt according to schedule, can prevent premature damage and ensure that the motorcycle continues to operate at its best performance. With adequate literacy, riders can not only save fuel and operational costs, but also support environmental sustainability by reducing emissions. Therefore, increasing public understanding of CVT technology is a strategic step to create more technologically aware and responsible motorcycle users.